2011
DOI: 10.1093/jxb/erq432
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cytosolic ascorbate peroxidase and Cu/Zn-superoxide dismutase for improved tolerance against drought stress

Abstract: In order to understand the role of cytosolic antioxidant enzymes in drought stress protection, transgenic tobacco (Nicotiana tabacum cv. Xanthi) plants overexpressing cytosolic Cu/Zn-superoxide dismutase (cytsod) (EC 1.15.1.1) or ascorbate peroxidase (cytapx) (EC 1.11.1.1) alone, or in combination, were produced and tested for tolerance against mild water stress. The results showed that the simultaneous overexpression of Cu/Znsod and apx or at least apx in the cytosol of transgenic tobacco plants alleviates, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
134
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(158 citation statements)
references
References 62 publications
11
134
0
8
Order By: Relevance
“…14 The different cellular compartment localization of the MeCu/ZnSOD and MeCAT1 enhanced scavenge ability of ROS both in the cytoplasm and peroxidsome, which is strongly consistent with the report by Faiz M et al 7 The increased SOD and CAT enzyme activities were able rapidly to scavenge ROS at the site of generation, as well as preventing the production of hydroxyl radicals, thereby enhancing stress tolerance. Thus, our study confirmed that improved cold and drought tolerance is probably attributed to enhanced expression of ROS-scavenging genes (jointly by SOD and CAT genes) resulting in increased ROS homeostasis under the abiotic stress.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…14 The different cellular compartment localization of the MeCu/ZnSOD and MeCAT1 enhanced scavenge ability of ROS both in the cytoplasm and peroxidsome, which is strongly consistent with the report by Faiz M et al 7 The increased SOD and CAT enzyme activities were able rapidly to scavenge ROS at the site of generation, as well as preventing the production of hydroxyl radicals, thereby enhancing stress tolerance. Thus, our study confirmed that improved cold and drought tolerance is probably attributed to enhanced expression of ROS-scavenging genes (jointly by SOD and CAT genes) resulting in increased ROS homeostasis under the abiotic stress.…”
supporting
confidence: 87%
“…13 Severe abiotic stress disrupts the metabolic balance of plant cells, resulting in a perturbed equilibrium between the production and the scavenging of ROS in the cytoplasm, chloroplasts and mitochondria in plants. Therefore, it is essential to have an efficient antioxidant network in order to scavenge ROS effectively and to maintain low levels of intracellular ROS pools.14 The different cellular compartment localization of the MeCu/ZnSOD and MeCAT1 enhanced scavenge ability of ROS both in the cytoplasm and peroxidsome, which is strongly consistent with the report by Faiz M et al 7 The increased SOD and CAT enzyme activities were able rapidly to scavenge ROS at the site of generation, as well as preventing the production of hydroxyl radicals, thereby enhancing stress tolerance. Thus, our study confirmed that improved cold and drought tolerance is probably attributed to enhanced expression of ROS-scavenging genes (jointly by SOD and CAT genes) resulting in increased ROS homeostasis under the abiotic stress.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…During water stress reduction was found between osmotic potential (Zhang et al (2015), water potential (Iqubal et al (2014) and relative water content (Vaezi et al 2010) in barley genotypes (Sharma et al, 2016;Aboughadareh et al 2017). When plant expose to adverse environment (drought) reactive oxygen species (ROS) such as superoxide (O 2 • ), hydrogen peroxide (H 2 O 2 ), hydroxyl radicals (OH • ) and singlet oxygen ( 1 O 2 ) are produced (Faize et al 2011). Multiple antioxidant enzymes like superoxide dismutases (SOD), catalases (CAT) and peroxidases (POX) are involved in the enzymatic scavenging of ROS (Apel and Hirt, 2004;de Carvalho, 2008;Farooq et al 2009).…”
Section: Issn: 2319-7706 Volume 7 Number 04 (2018)mentioning
confidence: 99%
“…Several studies on different enzymes have found that overexpression of only some of those enzymes enhanced performance under a particular stress (Foyer et al 1995;Payton et al 2001;Faize et al 2011;Le Martret et al 2011;Poage et al 2011). Photosynthetic processes are often the first physiological/metabolic processes to be inhibited by chilling temperature (Berry and Bjö rkman 1980).…”
Section: •ϫmentioning
confidence: 99%